International EFL/ESL Master Students’ Adaptation Strategies for Academic Writing Practices at Tertiary Level - Mehar Singh, Manjet Kaur (Journal of International Students, 2018)
The present research provides insights into the different forms of adaptation strategies employed by international graduate students to overcome the challenges faced in the academic writing practices and gain access to their disciplinary communities of practice at Master’s level. Qualitative data was collected through semi-structured in-depth focus group interviews. Respondents were 70 international graduate students enrolled in various Master-level programs. Semi-structured focus group interviews allowed the international graduate students to share their own experiences in the employment of suitable adaptation strategies to overcome the challenges faced in their academic writing practices in the Master programs. The adaptation strategies employed include enhancing their English language proficiency, referring to non-formal advisory services, and improving their academic writing style.